The crucial role of DNA-dependent protein kinase and myelin transcription factor 1-like protein in the miR-141 tumor suppressor network. Issue 21 (2nd November 2019) - Wang, Bo; Li, Dongping; Yao, Youli; Heyns, Mieke; Kovalchuk, Anna; Ilnytskyy, Yaroslav; Rodriguez-Juarez, Rocio; Bronson, Roderick T.; Metz, Gerlinde A.S.; Kovalchuk, Olga; Kovalchuk, Igor
ABSTRACT: Glioblastoma is the most aggressive brain tumor. Although miR-141 has been demonstrated to primarily function as a tumor suppressor in numerous malignancies, including glioblastoma, the mechanisms involved remain poorly understood. Here, it is shown that miR-141 is downregulated in glioblastoma cell lines and tissues and may exert its biological function via directly targeting myelin transcription factor 1-like ( MYT1L ). Using two glioblastoma cell lines that differ from each other by the functionality of DNA-dependent protein kinase (DNAPK), a functional involvement of DNAPK in the miR-141 tumor suppression network was observed. In M059K cells with a normal function of DNAPK, the enforced expression of miR-141 attenuated MYT1L expression and suppressed cell proliferation. Conversely, the inhibition of miR-141 expression promoted cell proliferation; however, in M059J cells with a loss-of-function DNAPK, miR-141 constitutively inhibited cell proliferation upon ectopic overexpression or inhibition. An overexpression of miR-141 suppressed M059J cell migration, while it had no effect on M059K. Furthermore, the ectopic expression of miR-141 induced an S-phase arrest in both cell lines, whereas the inhibition of miR-141 caused a G1 arrest in M059J and accelerated the S phase in M059K. An overexpression and suppression of miR-141 resulted in an aberrant expression of cell-cycle proteins, including p21. Moreover, MYT1L may be a transcription factor of p21 in p53-mutant cells, whereas DNAPK may function as a repressor of MYT1L. The findings revealed the crucial role of DNAPK in miR-141-mediated suppression of gliomagenesis and demonstrated that it may be a target molecule in miR-141-associated therapeutic interventions for glioblastoma.